(untitled) (Confluenţe Bibliologice, 2012)
In Open Access Week (22-28 October 2012) at Scientiﬁc Medical Library of SUMF „Nicolae Testemitanu” took place the conference „The impact of open access to information on the quality of the results of scientiﬁc research”, which was attended by about 50 representatives of the university libraries in R. Moldova (Chisinau, Balti, Lithuania, Kyrgyzstan). In the programme were presented 11 papers that focused on the topic of Open Access, policy, gold road, green road, creating institutional repository etc.